2018
DOI: 10.18844/gjpaas.v0i10.3742
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for professionalism of nursing students in clinical practices

Abstract: This is a descriptive study that aims to determine the factors affecting the professional behaviour of nursing students in clinical applications. The survey was conducted between 20 September and 20 December 2017 with the participation of 274 students studying in the Nursing Department of Health Sciences Faculty of a University. The data were collected using a questionnaire consisting of 18 questions and Nursing Students Professional Behaviours Scale (NSPBS). The mean age of the nursing students participated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…17 In the present study, professional behaviors of students who aimed to become a nurse and academician in the future were | 833 determined to increase. Also, Danaci et al 13 and Cevik and Khorshid 12 found that students who chose the profession willingly and did not consider changing their profession had higher levels of professional behaviors. Choosing a profession willingly and enjoying the profession are important criteria to apply it professionally.…”
Section: Nspbs Totalmentioning
confidence: 99%
See 2 more Smart Citations
“…17 In the present study, professional behaviors of students who aimed to become a nurse and academician in the future were | 833 determined to increase. Also, Danaci et al 13 and Cevik and Khorshid 12 found that students who chose the profession willingly and did not consider changing their profession had higher levels of professional behaviors. Choosing a profession willingly and enjoying the profession are important criteria to apply it professionally.…”
Section: Nspbs Totalmentioning
confidence: 99%
“…Choosing the profession of nursing willingly has an important place for nurses to implement their profession with pleasure, reveal their special abilities, and display a professional attitude by activating individuals. 13…”
Section: Nspbs Totalmentioning
confidence: 99%
See 1 more Smart Citation